Latamoxef dosing regimen adjustments and pharmaceutical care in pediatrics - Zhang, Ailin; Zuo, Meiling; Sun, Yuxuan; Chen, Jingtao; Zhu, Liqin; Liu, Wei (Frontiers in Pediatrics, 2024)
Latamoxef is a semi-synthetic, broad-spectrum oxacephem antibiotic used primarily to treat infectious diseases, but the adverse drug reactions, such as the risk of fatal bleeding, once caused physicians to use it less frequently. However, with the rise of antibiotic-resistant bacterial strains, latamoxef is being used again to treat infectious diseases, especially in pediatrics. The pharmacokinetic parameters of latamoxef are highly variable, given the changes in body composition, organ maturation, and development that occurs in pediatrics. Therefore, an appropriate dosing regimen is essential. Latamoxef dosing optimization in pediatrics should adequately account for current body weight, postnatal age, postmenstrual age, and different minimum inhibitory concentration (MIC) values. In addition, attention should also be paid to some of the adverse reactions associated with latamoxef, such as coagulation disorders and bleeding risks, disulfiram-like reactions, as well as hypersensitivity and anaphylactic shock. This review summarizes the dosing regimens and some key points of pharmaceutical care for latamoxef in pediatrics in order to provide a better reference for its application in clinical practice.